2016
DOI: 10.1002/ece3.2330
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal and group formation dynamics in a rare and endangered temperate forest bat (Nyctalus lasiopterus, Chiroptera: Vespertilionidae)

Abstract: For elusive mammals like bats, colonization of new areas and colony formation are poorly understood, as is their relationship with the genetic structure of populations. Understanding dispersal and group formation behaviors is critical not only for a better comprehension of mammalian social dynamics, but also for guiding conservation efforts of rare and endangered species. Using nuclear and mitochondrial markers, we studied patterns of genetic diversity and differentiation among and within breeding colonies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 74 publications
1
22
0
Order By: Relevance
“…The two closest colonies are located in Doñana National Park and Jerez de la Frontera, 60 and 77 km from María Luisa Park, holding a maximum of 40 and 150–200 individuals across years, respectively. Although genetic studies showed no differentiation between these colonies [ 26 ], our long-term monitoring of the three colonies does not support this idea. While many of the more than 300 females marked in María Luisa Park were recaptured within the same park across years [ 22 ], only one of these females visited Doñana (in 2001, 2003 and 2004), while two females marked in Doñana and Jerez visited María Luisa Park (2007 and 2017) and three females marked in Jerez visited Doñana (2004–2016), all for short periods of time.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The two closest colonies are located in Doñana National Park and Jerez de la Frontera, 60 and 77 km from María Luisa Park, holding a maximum of 40 and 150–200 individuals across years, respectively. Although genetic studies showed no differentiation between these colonies [ 26 ], our long-term monitoring of the three colonies does not support this idea. While many of the more than 300 females marked in María Luisa Park were recaptured within the same park across years [ 22 ], only one of these females visited Doñana (in 2001, 2003 and 2004), while two females marked in Doñana and Jerez visited María Luisa Park (2007 and 2017) and three females marked in Jerez visited Doñana (2004–2016), all for short periods of time.…”
Section: Discussionmentioning
confidence: 72%
“…Their annual survival rates were similar to those of other long-distance aerial-hawking bat species [ 25 ]. Genetically, this population is closely related to the two closest colonies of the species found in Jerez de la Frontera and Doñana National Park [ 26 ], located 60 km and 75 km from María Luisa Park, respectively.…”
Section: Methodsmentioning
confidence: 87%
“…(2009) further reported that females were loyal to their groups for at least five years, and that juveniles returned to their natal roosting areas along the study period. In a recent genetic analysis encompassing the region of Andalusia, Spain, and including four maternity colonies, we found that at least 31% of the females sampled shared their nursery colonies with mothers or daughters (Santos et al, 2016). However, the reasons for this high level of philopatry (despite the species' high dispersal ability, Burns & Broders, 2014) remain unclear.…”
Section: Introductionmentioning
confidence: 88%
“…All individuals were genotyped at 11 nuclear microsatellite loci: Nle 2, 3 and 6-11 (developed for Nyctalus leisleri, see Boston et al 2008); EF4 (developed for Eptesicus fuscus, Vohnof et al 2002); P20 and P217 (Kaňuch et al, 2007). All were tested in muscle tissue prior to genotyping (see Supplementary Methods for a detailed description of DNA extraction, amplification, sequencing, and microsatellite genotyping) and successfully employed in our previous study (Santos et al, 2016). Labelling followed Schuelke's procedure (2000).…”
Section: Molecular Methodsmentioning
confidence: 99%
See 1 more Smart Citation